Peran Guru Madrasah Diniyah dalam Meningkatkan Kemampuan Membaca Al-Qur’an Santri Melalui Metode Ummi di Madrasah Diniyah Tarbiyatul Ihsandesa - abdurrahmanwahid Wahid; Benny Prasetiya; Heri Rifhan Halili (Jurnal Pendidikan Dasar dan Keguruan, 2021)
Diniyah learning is non-formal learning that studies the Qur'an in children from an early age, and improves the morals listed in the Qur'an. Looking at current events, I am very concerned about the ability to study Qur'an. In this case the Tarbiyatul Ihsan Diniyah Education, Lemah Kembar, Probolinggo, there is a learning model, namely Al-ummi to make it easier for students to read the Qur'an. in addition, assisted with other facilities to support the activities of upgrading the Qur'an. The purpose of this research is to identify how the efforts of the diniyah Tarbiyatul Ihsan teacher in improving the skills of reading the Qur'an through the use of the ummi procedure. This research uses a qualitative method, and the type of research is problem research. The procedure used in collecting information is by means of monitoring (observation), selection (documentation), and question and answer (interview). Based on the research results, the efforts of the Diniyah Tarbiyatul Ihsan teacher in improving the skills of reading the Qur'an of students with the ummi procedure are repeating the readings that have been studied previously, classical form of reading and listening through repeated procedures, the memorization process is combined with conjunctions. share, and share encouragement.